BATIK WADASAN MOTIF, PAST AND PRESENT - Agus Nursalim; Tjetjep Rohendi Rohidi; Triyanto Triyanto; Sri Iswidiarti (Proceeding of International Conference on Art, Language, and Culture, 2017)
Batik motif in Indonesia has now undergone a change, the rapid demand of world batik products of Indonesia is now the design of batik motifs following market demand. Batik in Indonesia has increased quite rapid sales. Product innovation and marketing performance innovation have a positive effect on excellence in competition. Innovation from batik company in Indonesia is more on the creation of new motive product than continuing or continuing the existing classic motif product. Talking about the creation of new products, can not be separated from aspects of technology shifts, paradigms, skills and market structure. These aspects affect the company's strategy for its products to compete in the market. Hermeunitic Phenomenology Approach in this research will be used to examine the phenomena of the ongoing phenomenon in batik companies in Indonesia. This study aims to determine the process of shifting the visual form of traditional batik motifs after the market hegemony. After determining the puposeful sample, the researcher conducts the research by observing the role by involving himself in the event of the phenomenon, interviewing the phenomenon perpetrator, recording the events that occur in the batik industry environment outside the palace. The research finds the concept of problem solving in the creativity phenomenon of batik crafters to the wadasan motif by giving creative response form of innovation of new batik motif in order to meet market demand.